185k views
1 vote
Now, evaluate f (x) = 2x4 – 4x3 – 11x2 + 3x – 6 for x = –2.

f (–2) =

User Justdeko
by
6.7k points

2 Answers

1 vote

Answer:

8

Explanation:

f(- 2) = 8

f(-2) = 2 (-2) ^ 4 - 4 (- 2) ^ 3 - 11 (- 2) ^ 2 + 3*(- 2) - 6 = 2 * 16 + 32 - 44 - 6 - 6 = 8

Therefore the value of f(x) is 8 at x = - 2

User Drew Sears
by
6.2k points
0 votes

Answer:

f(- 2) = 8

Explanation:

To evaluate f(- 2) substitute x = - 2 into f(x) , that is

f(- 2) = 2
(-2)^(4) - 4(- 2)³ - 11(- 2)² +3(- 2) - 6

= 2(16) - 4(- 8) - 11(4) - 6 - 6

= 32 + 32 - 44 - 12

= 64 - 56

= 8

User Haliltprkk
by
5.3k points